The association between the deviation from balanced time perspective on adolescent pandemic mobile phone addiction: the moderating role of self-control and the mediating role of psychological distress - Zhang, Hao; Chen, Canjie; Zhang, Luoyi; Xue, Shuang; Tang, Wanjie (Frontiers in Psychology, 2024)
BACKGROUND: Few studies have examined the impact that the deviation from balanced time perspective (DBTP) had on mobile phone addiction during the COVID-19 normalization prevention and control phase. Therefore, this study sought to determine the associations between DBTP, depression and anxiety, self-control, and adolescent mobile phone addiction.The moderated mediating model was tested using the SPSS PROCESS model. The sample was 1164 adolescents from different regional areas of Sichuan, China. From February to March 2020, participants completed the Zimbardo time perspective inventory (ZTPI), the brief symptom inventory for physical and mental health (BSI-18), the self-control scale (SCS), and the Chinese version of the mobile phone addiction index (MPAI).The DBTP was significantly and positively correlated with mobile phone addiction, depressive and anxiety symptoms mediated the relationship between DBTP and mobile phone addiction, self-control moderated the indirect effect of DBTP on mobile phone addiction, and as the level of self-control increased, the effect of DBTP on anxiety and depression and the effect of depression and anxiety on mobile phone addiction weakened.During the COVID-19 pandemic, DBTP and lower self-control were risk factors for higher mobile phone addiction in adolescents. Therefore, guiding adolescents to balance their time perspective and enhance their self-control could strengthen their psychological well-being and reduce addictive mobile phone behaviors.